Pengaruh leverage, kebijakan dividen, struktur modal, dan keputusan investasi terhadap nilai perusahaan sektor industri makanan dan minuman di BEI tahun 2019-2022 - Simanjuntak, Lydia Maya Miranda; Widjaja, Indra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study aims to examine the effect of leverage, capital structure, dividends, and investment decisions on company value in the food and beverage sector on the IDX for the 2019-2022 period using a quantitative approach. There are 14 samples of companies in the food and beverage sector on the IDX for the 2019-2022 period. Then the data is processed with the SPSS26 program. The results obtained are (1) Leverage has an influence on company value. There is a negative correlation between leverage and company value, (2) Dividend Policy has an influence on company value. There is a negative correlation between capital structure and company value, (3) Capital structure has an influence on company value. There is a positive correlation between capital structure and company value, (4) Investment decisions have an influence on company value. There is a negative correlation between investment decisions and company value (5) Leverage, capital structure, capital structure and investment decisions have an influence on company value. There is a positive correlation between leverage, capital structure, capital structure and investment decisions and company value. Studi ini bertujuan untuk mengeksplorasi lebih dalam mengenai dampak. leverage, capital structure, dividen, dan investment decisions terhadap company value pada sektor food dan drink di BEI untuk periode 2019-2022. Kemudian pendekatan yang digunakan adalah pendekatan kuantitatif sengan sampel laporan keuangan dari 14 perusahaan pada sektor food dan drink di BEI untuk periode 2019-2022. Lalu data tersebut akan diolah dengan menggunakan program SPSS26. Sehingga, pada akhirnya menghasilkan suatu temuan yang dapat memberikan gambaran nyata bahwa (1) Leverage mempunyai pengaruh terhadap company value. Terdapat korelasi negatif antara leverage dan company value, (2) Dividend policy mempunyai pengaruh terhadap company value. Terdapat korelasi negatif antara dividend policy dan company value, (3) Capital structure mempunyai pengaruh terhadap company value. Terdapat korelasi positif antara capital structure dan company value, (4) Investment decisions mempunyai pengaruh terhadap company value. Terdapat korelasi negative antara investment decisions dan company value (5) Leverage, dividend policy, capital structure dan investment decisions mempunyai pengaruh terhadap company value. Terdapat korelasi positif antara leverage, dividend policy, capital structure dan investment decisions dan company value